Sustained complete response to first-line immunochemotherapy for highly aggressive TP53/MDM2-mutated upper tract urothelial carcinoma with ERBB2 mutations, luminal immune-infiltrated contexture, and non-mesenchymal state: a case report and literature review - Xu, Tianyuan; Guo, Hanxu; Xie, Jun; He, Yanyan; Che, Jianping; Peng, Bo; Yang, Bin; Yao, Xudong (Frontiers in Oncology, 2023)
Background: Upper tract urothelial carcinoma (UTUC) is a rare malignancy. The management of metastatic or unresectable UTUC is mainly based on evidences extrapolated from histologically homologous bladder cancer, including platinum-based chemotherapy and immune checkpoint inhibitor alone, whereas UTUC exhibits more invasiveness, worse prognosis and comparatively inferior response to treatments. First-line immunochemotherapy regimens have been attempted in clinical trials for unselected naïve-treated cases, but their efficacies relative to standard chemo-or immuno-monotherapy still remain controversial. Here, we present a case of highly-aggressive UTUC for whom comprehensive genetic and phenotypic signatures predicted sustained complete response to first-line immunochemotherapy. Case Presentation: A 50-year-old man received retroperitoneoscopic nephroureterectomy and regional lymphadenectomy for high-risk locally advanced UTUC. Postoperatively, he developed rapid progression of residual unresectable metastatic lymph nodes. Pathologic analysis and next-generation sequencing classified the tumor as highly-aggressive TP53/MDM2-mutated subtype with features more than expression of programmed death ligand-1, including ERBB2 mutations, luminal immune-infiltrated contexture and non-mesenchymal state. Immunochemotherapy combining gemcitabine, carboplatin and off-label programmed death-1 inhibitor sintilimab was initiated, and sintilimab monotherapy was maintained up to one year. Retroperitoneal lymphatic metastases gradually regressed to complete response. Blood-based analyses were performed longitudinally for serum tumor markers, inflammatory parameters, peripheral immune cells and circulating tumor DNA (ctDNA) profiling. The ctDNA kinetics of tumor mutation burden and mean variant allele frequency accurately predicted postoperative progression and sustained response to the following immunochemotherapy, which were mirrored by dynamic changes in abundances of ctDNA mutations from UTUC-typical variant genes. The patient remained free of recurrence or metastasis as of this publishing, over two years after the initial surgical treatment. Conclusion: Immunochemotherapy may be a promising first-line option for advanced or metastatic UTUC selected with specific genomic or phenotypic signatures, and blood-based analyses incorporating ctDNA profiling provide precise longitudinal monitoring.